Let's all get home safely: a commentary on NICE and SCIE guidelines (NG27) transition between inpatient hospital settings and community or care home settings. (2nd November 2016) - Winfield, Anna; Burns, Eileen
Abstract: Safe and appropriate transition between inpatient settings and the community is one of the major challenges facing the modern NHS. The National Institute for Health and Care Excellence in conjunction with the Social Care Institute for Excellence published guidance on this challenging area in December 2015. This commentary provides context, summary and discussion of the key areas covered. The guidance particularly emphasises the importance of a person-centred approach in which patients are individuals and equal partners in the multidisciplinary team who should be treated with dignity and respect. Additionally, communication and information sharing is crucial both on admission and when taking a proactive approach to discharge, including the role of the discharge coordinator in liaising with community teams and arranging follow-up post-discharge. Self-care and the significance of carers are also highlighted as valuable in facilitating safe discharge and reducing readmissions. It is clear that in older people with complex needs, safe appropriate transition between hospital and community settings has a positive impact on patients and their carers. Given the financial and capacity pressures facing the NHS, strategies to reduce readmissions and prevent delays in discharge are increasingly important. These guidelines are therefore both timely and advocated to improve care for older people.